Casanova in the Enlightenment : From the Margins to the Centre - Stefanovska, Malina (Book collections on Project MUSE., 2021)
"Illuminating the legend that Giacomo Casanova singlehandedly created in his famous--and at times infamous--autobiography, The History of My Life, this book provides a timely reassessment of Casanova's role and importance as an author of the European Enlightenment. From the margins of libertine authorship where he has been traditionally relegated, the various essays in this collection reposition Casanova at the heart of Enlightenment debates on medicine, sociability, gender, and writing. Based on new scholarship, this reappraisal of a key Enlightenment figure explores the period's fascination with ethnography, its scientific societies, and its understanding of gender, medicine, and women. Casanova is here finally granted his rightful place in cultural and literary history, a place which explains his enduring yet controversial reputation as a figure of seduction and adventure. "--